Increased expression of ACE2, the SARS-CoV-2 entry receptor, in alveolar and bronchial epithelium of smokers and COPD subjects - Jacobs, Merel; Van Eeckhoutte, Hannelore P.; Wijnant, Sara R.A.; Janssens, Wim; Joos, Guy F.; Brusselle, Guy G.; Bracke, Ken R. (The European respiratory journal, 2020)
Angiotensin-converting enzyme 2 (ACE2) has been identified as the cell entry receptor used by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1, 2]. Importantly, smokers and patients with COPD are at an increased risk of severe complications and a higher mortality upon SARS-CoV-2 infection [3]. We hypothesised that ACE2 expression is increased in lungs of smokers and patients with COPD, which may at least partially explain their higher risk of a more severe course of coronavirus disease 2019 (COVID-19). Therefore, we aimed to investigate the expression of ACE2 on both mRNA and protein level in a large number of lung tissue specimens of well-phenotyped subjects, including never-smokers, current smokers without airflow limitation, and patients with COPD. This study demonstrates increased protein levels of ACE2 in alveolar and bronchial epithelium of smokers and subjects with COPD, which might facilitate host cell entry of SARS-CoV-2 https://bit.ly/2ZazOrd